2018
DOI: 10.1159/000486286
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy and Outcomes in Trials of Nintedanib in Idiopathic Pulmonary Fibrosis

Abstract: Background: Cardiovascular comorbidities are frequent in patients with idiopathic pulmonary fibrosis (IPF), and many patients with IPF receive treatment with statins to reduce cardiovascular risk. Objectives: We investigated whether statin use at baseline was associated with differences in disease progression in placebo-treated patients or influenced the treatment effect of nintedanib in the INPULSIS® trials. Methods: Post-hoc subgroup analyses of patients receiving versus not receiving statins at baseline usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…A further post-hoc analysis examined the impact of statin use on the efficacy of nintedanib in the INPULSIS trials. 23 The treatment effect of nintedanib was consistent between patients receiving and not receiving statins.…”
Section: Nintedanib: Efficacy Evidencementioning
confidence: 87%
“…A further post-hoc analysis examined the impact of statin use on the efficacy of nintedanib in the INPULSIS trials. 23 The treatment effect of nintedanib was consistent between patients receiving and not receiving statins.…”
Section: Nintedanib: Efficacy Evidencementioning
confidence: 87%
“…In addition to their anti-in ammatory actions, our recent investigation showed that statins inhibit tissue damage by reducing extracellular matrix synthesis in airway mesenchymal cells [77,78]. Several studies have shown bene cial effects of statins in the treatment and recovery of patients with idiopathic pulmonary brosis and implied that statins improve lung function by acting on brosis mediators [79,80]. In addition, statins reduce mortality in these patients and those with interstitial lung disease [81].…”
Section: Discussionmentioning
confidence: 99%
“…Statins and anti-acid treatment were proposed to reduce incidence of AE-IPF, with prospective studies needed to confirm this hypothesis [ 14 , 54 ].…”
Section: Complicationsmentioning
confidence: 99%